2022
DOI: 10.1021/acs.chemmater.2c02984
|View full text |Cite
|
Sign up to set email alerts
|

A Stepwise-Confined Self-Reduction Strategy to Construct a Dynamic Nanocatalyst for Boosting Tumor Catalytic Therapy

Abstract: Fenton/Fenton-like reactions involve the transformation of hydrogen peroxide to hydroxyl radicals to kill tumors. However, the current Fenton/Fenton-like biocatalyst always suffers from low therapeutic efficacy owing to the slow reaction rate of low-valence metal/high-valence metal cycles. Herein, a "stepwise-confined self-reduction" strategy is proposed to construct a dynamic self-reduction dual-metal (Cu/Fe) nanocatalyst in the thiols/disulfide bonds-doped micellar-organosilica framework. The preferential se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…70,71 Although enhanced reaction activity is achieved, the catalytic selectivity is not well-controlled. Bimetallic NPs stabilized in aqueous micellar medium were further designed, [72][73][74][75] and their activity and selectivity can be affected by modulating the NP surface free energy, regulating the metal-organic interaction arising from surfactant modifiers and increasing the solubility of hydrogenation gas in water. Recently, Handa et al 76 reported that bimetallic Ni(0)Pd (0) NP catalyzed highly selective 1,4-reductions of a variety of Michael acceptors can be processed successfully under aqueous micellar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…70,71 Although enhanced reaction activity is achieved, the catalytic selectivity is not well-controlled. Bimetallic NPs stabilized in aqueous micellar medium were further designed, [72][73][74][75] and their activity and selectivity can be affected by modulating the NP surface free energy, regulating the metal-organic interaction arising from surfactant modifiers and increasing the solubility of hydrogenation gas in water. Recently, Handa et al 76 reported that bimetallic Ni(0)Pd (0) NP catalyzed highly selective 1,4-reductions of a variety of Michael acceptors can be processed successfully under aqueous micellar conditions.…”
Section: Introductionmentioning
confidence: 99%